2009
DOI: 10.1007/s11295-009-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Selection perspectives for genetic improvement of wood stiffness in hybrid larch (Larix x eurolepis Henry)

Abstract: Genetic variability of modulus of elasticity (MOE) was investigated in three genetic trials, including two progeny (16 years old) and one clonal (19 years old) trials of hybrid larch (Larix x eurolepis Henry). MOE was directly assessed on standing trees using the Rigidimeter, a bending device, and related to other traits including height, BH diameter and wood density. Mean MOE ranged from 5,183 to 9,228 MPa among families in the progeny trials and from 4,591 to 11,486 MPa in the clonal trial. Among traits stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
(23 reference statements)
2
13
0
Order By: Relevance
“…MOE D mirrored V Dir and gave similar genetic and phenotypic correlations. Phenotypic correlations between MOE D and growth attributes (HT, VOL, and DBH) in this study were similar to those reported by Pâques et al (2010).…”
Section: Genetic and Phenotypic Correlationssupporting
confidence: 90%
See 1 more Smart Citation
“…MOE D mirrored V Dir and gave similar genetic and phenotypic correlations. Phenotypic correlations between MOE D and growth attributes (HT, VOL, and DBH) in this study were similar to those reported by Pâques et al (2010).…”
Section: Genetic and Phenotypic Correlationssupporting
confidence: 90%
“…The Interestingly, there were no significant (p <0.05) negative phenotypic or genetic wood quality-growth trait correlations in this study. Pâques et al (2010) reported weak and nonsignificant phenotypic correlations between MOE and stem growth in hybrid larch wood (Larix × eurolepis Henry). Zobel and van Buijtenen (1989 ; Table 5) reported similar wood quality-growth trait relationships for Larix .…”
Section: Genetic and Phenotypic Correlationsmentioning
confidence: 99%
“…Nakada et al [14] reported no or weak positive clonal correlation between diameter and wood quality traits, and Koizumi et al [13] reported no clonal correlation between DBH and MOE in Larix kaempferi. On the other hand, negative genetic correlations between growth traits and wood quality traits (wood density and MOE) were reported in hybrid larch [16][17][18], and negative correlations between growth traits and wood quality traits have also been reported in several other species in Pseudotsuga menziesii [38][39][40], in Picea sitchenis [41], and in Pinus radiata [42]. Mishima et al [37] reported a very small but positive clonal correlation between DBH and SWV in C. japonica.…”
Section: Discussionmentioning
confidence: 99%
“…Fukatsu et al [15] reported a positive genetic correlation between wood density and basal area. In hybrid larch, a strong negative genetic correlation between wood density and radial growth rate, and a weak negative genetic correlation between MOE and DBH were reported in Larix gmelinii 9 L. kaempferi hybrids [16,17], and a strong negative genetic correlation between DBH and MOE was reported in Larix decidua 9 L. kaempferi hybrids [18]. To predict how the selection of a trait will affect correlated traits in the following generations of L. kaempferi, more research is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The Rigidimeter is particularly well-suited for ranking genotypes [96,98,[103][104][105]. Rigidimeter MOE values showed large phenotypic and genetic variability (in contrast to some other wood traits like density), moderate to high levels of heritability and low genetic by environment (GxE) interaction [106,107]. In a study in New Zealand (unpublished), trunk MOE measured with the Rigidimeter on standing radiata pine trees was found to be genetically variable and significantly correlated with acoustic velocity and stem knottiness index.…”
Section: Rigidimetermentioning
confidence: 99%